Efforts to Improve Knowledge and Skills of Splint Dressing with Simulation and Training Methods in Adolescents of Mandala Bhakti Health Vocational School Surakarta - Rahmad, Muhamad Nur; Rosyida, Nikma Alfi; Budiman, Amin Aji; Prastiwi, Firman (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2024)
ABSTRACT A fracture is a condition where a bone is cracked or broken due to trauma or physical impact. The strength and angle of physical exertion, the condition of the bone itself, and the soft tissue around the bone will determine whether the fracture is complete or incomplete. The impact of a fracture can cause bone deformity or disability and even death in the victim if help is not immediately provided, where splinting is one of the first aid measures that must be given to patients who experience a fracture. This community service activity aims to help increase the knowledge and skills of teenagers, especially PMR members, in providing first aid when they find a victim who has suffered a fracture. The method used in this activity uses power point media when providing education, then continues with demonstrations and direct simulations for participants on how to apply splints to patients who have fractures. The results of the activity showed the enthusiasm of the participants in carrying out the splint dressing demonstration as well as an increase in participants' knowledge and skills in carrying out the splint dressing, namely during the pre-test, 25% of their knowledge and skills were good, increasing to 81.25% after the education and post-test were carried out. So it can be concluded that providing health education and demonstrations regarding dressing splints really helps teenagers in increasing their knowledge and skills in dressing splints. Keywords: Skills, Splinting, Training